Design of reliable universal QCA logic in the presence of cell deposition defect. Issue 8 (3rd August 2017) - Sen, Bibhash; Mukherjee, Rijoy; Mohit, Kumar; Sikdar, Biplab K.
ABSTRACT: The emergence of Quantum-dot Cellular Automata (QCA) has resulted in being identified as a promising alternative to the currently prevailing techniques of very large scale integration. QCA can provide low-power nanocircuit with high device density. Keeping aside the profound acceptance of QCA, the challenge that it is facing can be quoted as susceptibility to high error rate. The work produced in this article aims towards the design of a reliable universal logic gate (r-ULG) in QCA (r-ULG along with the single clock zone and r-ULG-II along with multiple clock zones). The design would include hybrid orientation of cells that would realise majority and minority, functions and high fault tolerance simultaneously. The characterisation of the defective behaviour of r-ULGs under different kinds of cell deposition defects is investigated. The outcomes of the investigation provide an indication that the proposed r-ULG provides a fault tolerance of 75% under single clock zone and a fault tolerance of 100% under dual clock zones. The high functional aspects of r-ULGs in the implementation of different logic functions successfully under cell deposition defects are affirmed by the experimental results. The high-level logic around the multiplexer is synthesised, which helps to extend the design capability to the higher-level circuit synthesis.